Contribution of Application of the Hazton and Jajar Legowo Methods to Rice Farming in Lolori Village, West Halmahera Regency - Ekaria, Ekaria; Mamulati, Irman (Agrikan Jurnal Agribisnis Perikanan, 2020)
This research was carried out in Lolori Village, Jailolo District, West Halmahera Regency, with the research time starting from April 2020 with one farmer group using the hazton method as many as 21 respondents and one farmer group using the jajar legowo method as many as 21 respondents. The results showed that the total income of lowland rice farmers with the Hazton cropping system was Rp. 28,891,175 /ha/planting season and the total income of paddy rice farmers with the jajar legowo planting system is Rp. 14,041,858/ha/planting season. Based on the results of the calculation of the difference in income of lowland rice farming with the Hazton and jajar legowo cropping systems, it is known that there is a significant difference in income between lowland rice farming with the hazton and jajar legowo cropping systems. .85 so H0 is rejected. And the largest income contribution in the application of the lowland rice planting system is using the Hazton planting system, which is 89% compared to the row legowo planting system, which is 78%.